Death Rate Analysis Due to Suicide - Syaiful Nizam Abu Hassan, Mohd; Khairul Amri Kamarudin, Mohd; Hafiz Md Saad, Muhammad; Abd Wahab, Noorjima; Halimatul Nur Adeni Sabri, Ummi; Nurkhairunnisa Wan Hashin, Wan; Syakinah Wahab, Nor; Nur Syazwani Raja Md Yusoh, Raja; Amalina Fatehah Yusoff, Nur; ., . (International Journal of Engineering and Technology, 2018)
Suicide is an act committed by an individual consciously aiming to end or eliminate the life itself. But when their act of suicide failed they were categorized as attempted suicide. This is not a new thing for modern society today. According to official statistics, there are about one million people committed suicide around the world within one year, and this amount does not include those killed by others or those killed in the war. Therefore, the study aims to analyze suicide rates recorded by the five countries with the highest rates of suicide and assess the differences in the frequency of suicide cases between men and women. In addition, this study will identify the methods or methods used to commit suicide and what are the risk factors that cause an individual to decide to end his life. The methods used to commit suicide will also be explained more clearly. Suicide symptoms can be serious in society if preventive measures at the early stage are not taken. This study is expected to help future researchers to find ways to save these unlucky ones from doing something that can harm themselvesÂ Â